DO WE NEED TO BE PRODUCTIVE DURING A GLOBAL PANDEMIC - COVID 19 ? - Putra, Halim Dwi (International Journal of Psychosocial Rehabilitation, 2020)
This paper provides the writer’s views and opinions regarding the covid 19 outbreak which requires peoples working from home for more productive results. Pushing yourself to be productive every day all through a total global disaster is exhausting. Why do we want to fill our day with tons of things simply to feel like we deserve to relax at the end of it? This wasn’t an unfamiliar feeling. We all favor playing a pivotal function at some point of this pandemic and come out of this with something to exhibit the world. The writer informs that it is good enough to revel in this second the pandemic has supplied to simply be nevertheless and relax. This opinion is from the point of view of students who are given assigning tasks that require and leave the house to get the material. The writer as a doctoral student at the university saw many complaints from student. Many students first grade complained that many assignments made them even more stressed.